2020
DOI: 10.1108/lht-03-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

A new decade of uses for geographic information systems (GIS) as a tool to research, measure and analyze library services

Abstract: PurposeThe purpose of this paper is to explore library research that uses geographic information systems (GIS) as a tool to evaluate library services and resources to ascertain current trends and establish future directions for this growing research area.Design/methodology/approachThe study searched full text for geographic information systems in two databases: Library and Information Science Source (LISS) and Library, Information Science and Technology Abstracts (LISTA), replicating the method used in a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…An analysis of what has been contributed indicates trajectories of where it appears to be headed, what opportunities exist to inform other research and what literature gaps exist and persist. Previous research has suggested that systematic literature reviews are helpful for identifying themes in an emerging area of the LIS discipline (Bishop and Mandel, 2010;Mandel et al, 2020). As such, this study conducts a literature review in order to address this literature gap for social justice in LIS by asking the following research questions:…”
Section: Library and Information Sciencementioning
confidence: 99%
“…An analysis of what has been contributed indicates trajectories of where it appears to be headed, what opportunities exist to inform other research and what literature gaps exist and persist. Previous research has suggested that systematic literature reviews are helpful for identifying themes in an emerging area of the LIS discipline (Bishop and Mandel, 2010;Mandel et al, 2020). As such, this study conducts a literature review in order to address this literature gap for social justice in LIS by asking the following research questions:…”
Section: Library and Information Sciencementioning
confidence: 99%
“…The technology also supports the planning of pedestrian-friendly spaces by analyzing foot traffic patterns and identifying areas that require improved pedestrian infrastructure, such as sidewalks, crossings, and public squares. Additionally, GIS tools aid in designing cycling networks by identifying the most suitable routes that ensure safety and connectivity for cyclists [3]. By providing a data-driven approach to traffic management, GIS helps in creating urban spaces that prioritize accessibility and minimize congestion, enhancing the overall quality of urban life.…”
Section: Traffic Flow and Accessibilitymentioning
confidence: 99%
“…Mandel et al . (2023) analyzed geographic information systems (GIS) research in two databases, Library and Information Science Source (LISS) and Library Information Science and Technology Abstracts (LISTA), and found growth in the last decade for library research using GIS to analyze service areas and to manage facilities and collections.…”
Section: Advances In Library Information Managementmentioning
confidence: 99%
“…Besides, readers may be interested in issues related to library promotion and marketing (Chan et al, 2020;Cheng et al, 2020;Fong et al, 2020;Kwan et al, 2023;Lam et al, 2019Lam et al, , 2023Liu et al, 2023;Sahli et al, 2023;W ojcik, 2022;Wu and Yang, 2022). Mandel et al (2023) analyzed geographic information systems (GIS) research in two databases, Library and Information Science Source (LISS) and Library Information Science and Technology Abstracts (LISTA), and found growth in the last decade for library research using GIS to analyze service areas and to manage facilities and collections. Readers may also be interested in other bibliometrics research and reviews on library-related subjects (Alcaraz Mart ınez et al, 2022;Borgohain et al, 2022;Nadi-Ravandi and Batooli, 2023;Ding et al, 2021a;Feng et al, 2022a;Kim et al, 2021;Lee, 2021;Nugroho et al, 2023;Nwankwo et al, 2022;Shahzad and Khan, 2022;Wijewickrema, 2023;Zhang et al, 2023b).…”
mentioning
confidence: 99%